Prospects of genetic testing for steroid-resistant nephrotic syndrome in Nigerian children: a narrative review of challenges and opportunities - Anigilaje, Emmanuel Ademola (Int J Nephrol Renovasc Dis, 2019)
The prevalence of childhood steroid-resistant nephrotic syndrome (SRNS) ranges from 35% to 92%. This steroid resistance among Nigerian children also reflects underlying renal histopathology, revealing a rare minimal-change disease and a varying burden of membranoproliferative glomerulonephritis and focal segmental glomerulosclerosis (FSGS). FSGS tends to progress to end-stage kidney disease, which requires dialysis and/or renal transplantation. While knowledge of the molecular basis of NS is evolving, recent data support the role of mutant genes that otherwise maintain the structural and functional composition of the glomerular filtration barrier to account for many monogenic forms of FSGS. With the advent of next-generation sequencing, >39 genes are currently associated with SRNS, and the number is likely to increase in the near future. Monogenic FSGS is primarily resistant to steroids, and this foreknowledge obviates the need for steroids, other immunosuppressive therapy, and renal biopsy. Therefore, a multidisciplinary collaboration among cell biologists, molecular physiologists, geneticists, and clinicians holds prospects of fine-tuning the management of SRNS caused by known mutant genes. This article describes the genetics of NS/SRNS in childhood and also gives a narrative review of the challenges and opportunities for molecular testing among children with SRNS in Nigeria. For these children to benefit from genetic diagnosis, Nigeria must aspire to have and develop the manpower and infrastructure required for medical genetics and genomic medicine, leveraging on her existing experiences in genomic medicine. Concerted efforts can be put in place to increase the number of enrollees in Nigeria’s National Health Insurance Scheme (NHIS). The scope of the NHIS can be expanded to cater for the expensive bill of genetic testing within or outside the structure of the National Renal Care Policy proposed by Nigerian nephrologists.